RESEARCH IN THE LIGHT OF ISLAM: ETHICAL FOUNDATIONS AND METHODOLOGICAL INSIGHTS (International Journal of Food and Nutritional Sciences, 2022)
Research methodology plays an important role in shaping the quality, integrity, and relevance. From the Islamic perspective, pursuing knowledge is not merely a scholarly endeavor but a virtuous act imbued with ethical considerations. Researchers are guided by the principles of honesty, fairness